2019
DOI: 10.1186/s13104-019-4675-4
|View full text |Cite
|
Sign up to set email alerts
|

Malignant mesothelioma in construction workers: the Apulia regional mesothelioma register, Southern Italy

Abstract: Objective Asbestos was widely used in construction in both a friable and a compact form until the 1990s, before its use was banned. Today, many of these materials are still in situ and represent a source of risk for construction workers. The objective of the study was to analyse the cases of mesothelioma arising among construction workers registered in the Apulia regional register of mesothelioma. Results For the period 1993–2018, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 52 publications
1
16
0
2
Order By: Relevance
“…Regarding the cited study of Marinaccio et al 2010 [5], of which some of us are co-authors, we would like to note that in table 3 of the work, 50% of MMTVT cases are reported in economic sectors such as in the construction, steel, and transport construction and maintenance industries wherein the use of asbestos is well known in the technological cycles as well as (especially in past years, and this agrees with the latency time) the failure to comply with safety requirements to protect the health of workers [6].…”
mentioning
confidence: 72%
“…Regarding the cited study of Marinaccio et al 2010 [5], of which some of us are co-authors, we would like to note that in table 3 of the work, 50% of MMTVT cases are reported in economic sectors such as in the construction, steel, and transport construction and maintenance industries wherein the use of asbestos is well known in the technological cycles as well as (especially in past years, and this agrees with the latency time) the failure to comply with safety requirements to protect the health of workers [6].…”
mentioning
confidence: 72%
“…During the production of coke, large quantities of coke oven gas are emitted, resulting in consequent environmental pollution and exposure of both workers and the general population, similar to other productive activities [1][2][3]. The working environment at a coke plant can negatively affect the workers exposed to coke oven emissions (COE) containing polycyclic aromatic hydrocarbons (PAHs), which are formed and released into the environment via the pyrolysis of coke.…”
Section: Coke Plants and Pahsmentioning
confidence: 99%
“…Coke oven workplaces (top side, coke side, and push side) are characterized by a higher carcinogenic risk than other coke plant workplaces [11]. PAHs in the air of different production sectors in coking plants were measured, and the results showed that the total PAH concentrations ranged from 11.75 to 46.66 micrograms/m 3 ; the benzo(a)pirene (BaP) concentration was 0.050-1.054 micrograms/m 3 in the following areas in descending order: the outlet of the coke oven, the top of the coke oven, the gate, and the point of coke flame out. BaP pollution in the air in the top and outlet of the coke oven was much heavier than that in the soot and air of the arterial road [12].…”
Section: Coke Plants and Pahsmentioning
confidence: 99%
“…Malignant pleural mesothelioma (MPM) is an aggressive tumor of mesothelial origin that occurs after a long latency period following asbestos exposure often comprising several decades [ 1 , 2 , 3 , 4 ]. This tumor occurs mostly in the pleura (>75%) and less often in the peritoneum (10–20%) or pericardium (1%) [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%